Post COVID-19 Psychological Impacts on Recovered Teachers Working in Different Level of Educational Institutions of District Karak, Khyber Pakhtunkhwa, Pakistan - Kalim Ullah; Ayesha Ihsan Qazi; Professor Dr. Muhammad Anwar (Zien Journals, 2022)
The current study was carried out with the aim to examine and access post COVID-19 psychological impact on individual working in educational institutions of district Karak, Khyber Pakhtunkhwa. Post traumatic stress of that disease results in fear, stress, anxiety and other psychological disturbance. In such circumstances teaching where close contact environment is the need however, with a fear of insecurity and exposition to disease by contact. That’s why a study is necessary to cope the problems in light of observations. The present research work was designed on questionnaire base of research to teachers for exploring the the milling and psychological impacts over their teaching profession. Over analysis study of psychological indices were recorded as, fear 75%, lack of sleep 73%, depression 86%, stress 84%, anxiety 82%, grief 93%, anger 80% and headache 55%. It was recorded that the highest psychological distress due to COVID-19 is grief 42/45 (93%) among the sample population while the lowest is headache 25/45 (55%). This showed that Coivd-19 made lives of district Karak limited and their is no any healthy recreation opportunities for them to be mentally attached there.
Keywords: Post; COVID-19; Psychological; Educational Institutes